2020
DOI: 10.48550/arxiv.2002.00358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Moduli space of $λ$-connections

Abstract: Let X be a compact Riemann surface of genus g ≥ 3. Let M Hod denote the moduli space of stable λ-connections over X and M ′ Hod ⊂ M Hod denote the subvariety whose underlying vector bundle is stable. Fix a line bundle L of degree zero. Let M Hod (L) denote the moduli space of stable λ-connections with fixed determinant L and M ′ Hod (L) ⊂ M Hod (L) be the subvariety whose underlying vector bundle is stable. We show that there is a natural compactification of M ′ Hod and M ′ Hod (L), and study their Picard grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…, it has been shown that there are no nonconstant algebraic functions on M λ (X, r, O X ) [35,43]. Hence, σλ is a constant map, in other words, σ maps the fiber π −1 (λ) to another fiber π −1 (λ ′ ) for some λ ′ ∈ C. By Riemann-Hilbert correspondence, M dR (X, r, O X ) is biholomorphic to the affine variety M B (X, SL(2, C)), hence it does not contain any compact submanifold of positive dimension, however, by properness of Hitchin map [20,21,39], M Dol (X, r, O X ) contains many compact submanifolds of positive dimensions, namely, π −1 (λ) is not biholomorphic to π −1 (0) for any λ ∈ C * .…”
Section: Balanced Metricmentioning
confidence: 99%
“…, it has been shown that there are no nonconstant algebraic functions on M λ (X, r, O X ) [35,43]. Hence, σλ is a constant map, in other words, σ maps the fiber π −1 (λ) to another fiber π −1 (λ ′ ) for some λ ′ ∈ C. By Riemann-Hilbert correspondence, M dR (X, r, O X ) is biholomorphic to the affine variety M B (X, SL(2, C)), hence it does not contain any compact submanifold of positive dimension, however, by properness of Hitchin map [20,21,39], M Dol (X, r, O X ) contains many compact submanifolds of positive dimensions, namely, π −1 (λ) is not biholomorphic to π −1 (0) for any λ ∈ C * .…”
Section: Balanced Metricmentioning
confidence: 99%